Bangladesh economy at cross-road: policy directions for the future - Islam, Mirza Azizul (© 2013 The American Chamber of Commerce in Bangladesh (AmCham), 2016)
This article was published in Journal of the American Chamber of Commerce in Bangladesh [© 2014 Journal of the American Chamber of Commerce in Bangladesh] and the definite version is available at :http://www.amchambd.org/esoft-cms/media/AmCham%20Bangladesh%20Journal%20Issue%20April%202013.pdf The article website is at: http://www.amchambd.org/view_content.php?pageid=499